APP depletion alters selective pre- and post-synaptic proteins - Martinsson, Isak; Capetillo-Zarate, Estibaliz; Faideau, Mathilde; Willén, Katarina; Esteras, Noemi; Frykman, Susanne; Tjernberg, Lars O.; Gouras, Gunnar K. (Molecular and cellular neuroscience, 2019)
The normal role of Alzheimer's disease (AD)-linked amyloid precursor protein (APP) in the brain remains incompletely understood. Previous studies have reported that lack of APP has detrimental effects on spines and electrophysiological parameters. APP has been described to be important in synaptic pruning during development. The effect of APP knockout on mature synapses is complicated by this role in development. We previously reported on differential changes in synaptic proteins and receptors in APP mutant AD transgenic compared to wild-type neurons, which revealed selective decreases in levels of pre- and post-synaptic proteins, including of surface glutamate receptors. In the present study, we undertook a similar analysis of synaptic composition but now in APP knockout compared to wild-type mouse neurons. Here we demonstrate alterations in levels of selective pre- and post-synaptic proteins and receptors in APP knockout compared to wild-type mouse primary neurons in culture and brains of mice in youth and adulthood. Remarkably, we demonstrate selective increases in levels of synaptic proteins, such as GluA1, in neurons with APP knockout and with RNAi knockdown, which tended to be opposite to the reductions seen in AD transgenic APP mutant compared to wild-type neurons. These data reinforce that APP is important for the normal composition of synapses. •Elevations in selective synaptic proteins in APP KO neurons and brains rather than decreases reported with AD•Increased AMPA receptor GluaA1 in APP KO neurons and brains and with RNAi APP knockdown in wild-type neurons•Reduced spine density and dendrite branching with APP KO, despite PSD-95 and synaptophysin elevations but drebrin reduction